The encyclopedia of mammals - Macdonald, David W., (David Whyte) (New York : Facts on File, 1984)
Text and over 800 full-color illustrations detail every living species of mammal.
"An Andromeda book"--T.p. verso.
Includes bibliographical references and index.
School Library Journal.
Wilson's Public Library.
Wilson's Senior High School.
7-10.
Keywords: Mammals -- Encyclopedias; Mammals -- Encyclopedias